1855 La. Acts 148 - (:unkn) unknown (My University, 1855)
Ch. 120: Prohibited the concealed carrying of "pistols, bowie knife, dirk, or any other dangerous weapon." Violators fined not exceeding one thousand dollars or no more than three months imprisonment.
Keywords: CARRY - CONCEALED